2021
DOI: 10.3389/fmed.2021.654197
|View full text |Cite
|
Sign up to set email alerts
|

The Possible Non-Mutational Causes of FVIII Deficiency: Non-Coding RNAs and Acquired Hemophilia A

Abstract: Hemophilia type A (HA) is the most common type of blood coagulation disorder. While the vast majority of cases are inherited and caused by mutations in the F8 gene, recent data raises new questions regarding the non-heritability of this disease, as well as how other molecular mechanisms might lead to the development of HA or increase the severity of the disease. Some data suggest that miRNAs may affect the severity of HA, but for some patients, miRNA-based interference might cause HA, in the absence of an F8 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 52 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…Two cases of AH were described as F8 mutant with point mutation. Thus, an epigenetic evaluation of AH cases could bring new diagnostic/detection methods in the spotlight 10,23 . AH may be triggered by other autoimmune diseases, drug side effects, different types of cancer; however, some of AH cases remain idiopathic and deep investigations are needed to improve patient management to avoid ICU hospitalisation due to haemorrhage situations 24–26 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Two cases of AH were described as F8 mutant with point mutation. Thus, an epigenetic evaluation of AH cases could bring new diagnostic/detection methods in the spotlight 10,23 . AH may be triggered by other autoimmune diseases, drug side effects, different types of cancer; however, some of AH cases remain idiopathic and deep investigations are needed to improve patient management to avoid ICU hospitalisation due to haemorrhage situations 24–26 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, due to the high variability in F8 mutational status, the link between epigenetics and HA must be further investigated and certain interactions must be confirmed. [7][8][9][10] In our study, we investigated the transcriptomic signature in RNAs from the plasma of two AH patients, six classical haemophilia patients (three mild and three severe) and compared them to two healthy donors; by RNA-sequencing to highlight relevant differentially expressed transcripts. We observed that haemoglobin subunit alpha 1 and both coding and non-coding RNAs show different expressions in AH compared to all other investigated groups, potentially being a reliable biomarker candidate for predicting AH development.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hemophilia is a group of rare bleeding disorders, recessive genetic diseases linked to the X chromosome (1,2). Due to the lack of coagulation factors from the intrinsic pathway, patients present with prolonged bleeding after injury, easy bruising, or even spontaneous bleeding (3).…”
Section: Introductionmentioning
confidence: 99%